Marriage Dissolution and Health Amongst the Elderly: The Role of Social and Economic Resources - Baxter, Janeen; Western, M; Hewitt, B; Turrell, G (My University, 2004)
The elderly population in Australia is witnessing an increase in the number and proportion of separated and divorced people and a decline in the proportion who are married. This shift may have implications for health and aged care spending over the next few decades as previous (mainly overseas) research has shown that the non-married have poorer health than the married. We examine the association between marital status and self reported general health in a population sample of Australian men and women aged 60 and over. Our results show a strong association between marital status and health among elderly women, where the divorced, widowed, and never married report better health than the married. Separated elderly women, however, reported poorer health than married women. We argue that, based on our findings, separated women may represent an important target group for policy intervention. By contrast our study only found a weak association between marital status and health among elderly men.
Keywords: Relationships -- Dissolution; Relationships; Ageing; Health; Ageing; Health and wellbeing; Ageing; Health